Strategic Human Capital Management and Employee Satisfaction: A Moderated Mediation Analysis of Self-Efficacy and Cultural Values - Rashid, Humaira; Shah , Syed Afzal Moshadi; Nepal , Prashanna; Arif, Sania; Koka, Nisar Ahmad; Khan, Faisal; Ozturk, Ilknur; Zaman, Khalid (International Review of Management and Marketing, 2026)
The study examines the role of Strategic Human Capital Management (SHCM) in advancing higher education performance and employee satisfaction in Pakistan. Human resource practices have been studied extensively in the past, while few studies have examined how SHCM influences workplace dynamics in complex academic settings, particularly in developing countries. The study employed a mixed-methods approach, examining the responses of 498 stakeholders, including academics, administrators, and graduate scholars, on SHCM processes. Survey results indicate that fair compensation, inclusive management, and supportive leadership are key to fostering job performance. Additionally, cultural values influence the employer-employee relationship, and self-efficacy mediates the impact of SHCM approaches on employee satisfaction. Qualitative observations highlight the importance of participatory environments and professional advancement. The findings illustrate practical ways for university administrators to develop effective and culturally sensitive HRM systems, contributing to human capital research.